2015
DOI: 10.1159/000381743
|View full text |Cite
|
Sign up to set email alerts
|

Conjunctival Attachment of a Live Paralysis Tick, Ixodes holocyclus, in a Child: A Case Report

Abstract: We describe a rare clinical finding of conjunctival tick attachment in a child. A 10-year-old boy presented to the clinic with right-eye itch. He was found to have a live tick firmly attached to his right temporal conjunctiva. The tick was identified as the larval stage of the paralysis tick, Ixodes holocyclus. The tick was removed completely by conjunctival excision. Although various methods of removing a tick have been described in the literature, the goal of treatment is the safe and complete removal of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
(26 reference statements)
0
5
0
Order By: Relevance
“…But it has been revealed that chemical substances may cause irritation and encourage the tick to release infectious saliva as a reaction. The most effective technique is the mechanical intervention by using a blunt, medium-tip angled forceps, which is a quick, simple, and safe treatment modality, especially for conjunctival tick attachment [2,6,14] . If the tick attaches deeply into the host tissue, conjunctival excision is the best treatment modality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But it has been revealed that chemical substances may cause irritation and encourage the tick to release infectious saliva as a reaction. The most effective technique is the mechanical intervention by using a blunt, medium-tip angled forceps, which is a quick, simple, and safe treatment modality, especially for conjunctival tick attachment [2,6,14] . If the tick attaches deeply into the host tissue, conjunctival excision is the best treatment modality.…”
Section: Discussionmentioning
confidence: 99%
“…Although ticks are a recognized vector for disease spread through the penetration of the skin, their attachment to the conjunctiva is a rather infrequent entity with little mention in the literature. Only several cases of conjunctival tick bites have been reported in the literature [2,4,6] .…”
mentioning
confidence: 99%
“…In some cases, the tick was attached to children in unusual locations on the body, such as on the conjunctiva of the eye (Teong et al . 2015). Most of the time, however, the clinical notes provided no details on where on the body the tick was attached.…”
Section: Discussionmentioning
confidence: 99%
“…Larva of I. holocyclus cannot feed on humans; however, their attachments to humans usually cause no more than localized dermatitis. For example, a larva of I. holocyclus was found attached to right temporal conjunctiva of a 10-year-old boy from Sydney in New South Wales (Teong et al, 2015). The only symptoms developed were eye itch and conjunctival vessel dilatation around the organism.…”
Section: Other Tick-borne Diseasesmentioning
confidence: 99%